2003
DOI: 10.1007/s00253-003-1224-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aeration and organic loading rates on degradation of trichloroethylene in a methanogenic-methanotrophic coupled reactor

Abstract: The effects of four aeration and four organic loading (OLR) rates on trichloroethylene (TCE) degradation in methanogenic-methanotrophic coupled reactors were studied using ethanol as the carbon source for the methanogens. Microcosm and PCR studies demonstrated that methanotrophs capable of mineralizing TCE and methanogens were present in the biomass throughout the study. The gene for the particulate form of methane monooxygenase (pMMO) was detected by PCR, but not that for the soluble form (sMMO). TCE minerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The final volume of 20 µL PCR reaction contained 0.2 µL PfuUltra II fusion HS DNA polymerase (Agilent Technologies, Santa Clara, California, USA), 50 µM each forward and reverse primer, 25 µM each dNTPs (Thermo Scientific, Waltham, Massachusetts, USA), 10 µg mL −1 BSA (Thermo Scientific, Waltham, Massachusetts, USA) and 1 ng template DNA. After initial denaturation for 2 min at 95 • C, DNA was amplified in 30 cycles of 30 s 95 • C denaturation, 30 s 55 • C annealing, and 30 s at 72 • C for extension, with a final extension of 2 min at 72 • C. The pmoA subunit of the particulate monooxygenase (pMMO) was amplified with primer pair 189f (5 -xx-GGNGACTGGGACTTCTGG-3 ) and mb661r (5 -yy-CCGGMGCAACGTCYTTACC-3 ) (Holmes et al, 1999;Lyew and Guiot, 2003). The PCR conditions were the same as described for the V4-V5 amplicon.…”
Section: Nucleic Acid Extraction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The final volume of 20 µL PCR reaction contained 0.2 µL PfuUltra II fusion HS DNA polymerase (Agilent Technologies, Santa Clara, California, USA), 50 µM each forward and reverse primer, 25 µM each dNTPs (Thermo Scientific, Waltham, Massachusetts, USA), 10 µg mL −1 BSA (Thermo Scientific, Waltham, Massachusetts, USA) and 1 ng template DNA. After initial denaturation for 2 min at 95 • C, DNA was amplified in 30 cycles of 30 s 95 • C denaturation, 30 s 55 • C annealing, and 30 s at 72 • C for extension, with a final extension of 2 min at 72 • C. The pmoA subunit of the particulate monooxygenase (pMMO) was amplified with primer pair 189f (5 -xx-GGNGACTGGGACTTCTGG-3 ) and mb661r (5 -yy-CCGGMGCAACGTCYTTACC-3 ) (Holmes et al, 1999;Lyew and Guiot, 2003). The PCR conditions were the same as described for the V4-V5 amplicon.…”
Section: Nucleic Acid Extraction and Sequencingmentioning
confidence: 99%
“…Measurements were performed in fast measurement mode. Dissolved methane concentrations were calculated as described in Magen et al (2014), with the equilibrium constant according to Yamamoto et al (1976).…”
Section: Analytical Procedures 241 Methane Concentration and Stablementioning
confidence: 99%
“…PhyloChip analysis from the same study also showed a shift in the structure of the microbial community with distance from the source well from bacteria involved in methanogenesis and reductive dechlorination to methanotrophic bacteria. The co-existence of aerobic methanotrophs and anaerobic methanogens in TAN-29 and TAN-35 planktonic samples is not unusual as methanogens can survive under aerobic conditions by inhabiting biofilms (Lyew and Guiot 2003). Likewise methanotrophs are capable of going dormant under anoxic conditions (Roslev and King 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The following primers were used for the amplification of pMMO (standard curve r 2 = 0.999), 189f (5 0 -GGNGACTGGGACTTC TGG-3 0 ) and mb661r (5 0 -CCGGMGCAACGTCY TTACC-3 0 ) (Lyew and Guiot 2003;Holmes et al 1995). The mmoX portion of sMMO (standard curve r 2 = 0.999) was amplified using primer pair 536f (5 0 -CGCTGTGGAAGGGCATGAAGCG-3 0 ) and 898r (5 0 -GCTCGACCTTGAACTTGGAGCC-3 0 ) (Fuse et al 1998;Lyew and Guiot 2003). Amplification of methanol dehydrogenase genes (standard curve r 2 = 0.994) was performed using the primer pair mxa f1103 (5 0 -GCGGCACCAACTGGGGCTGGT-3 0 ) and mxa r1561 (5 0 -GGGCAGCATGAAGGGC TCCC-3 0 ) (McDonald and Murrell 1997).…”
Section: Dna Extractions For Qpcrmentioning
confidence: 99%
“…The pmoA subunit of the particulate monooxygenase (pMMO) was amplified with primer pair 189f (5´-xx-GGNGACTGGGACTTCTGG-3´) and mb661r (5´-yy-CCGGMGCAACGTCYTTACC-3´) (Holmes et al, 1999;Lyew and Guiot, 2003). The PCR conditions were the same as described for the V4V5 amplicon.…”
Section: Nucleic Acid Extraction and Sequencingmentioning
confidence: 99%